WCDMA forward link capacity improvement by using adaptive antenna with genetic algorithm assisted MDPC beamforming technique - Tiong, Sieh Keong; Ismail, Mahamod; Hassan, Azmi (Asian Network for Scientific Information, 2006)
Capacity has always been an issue to any generation of mobile communication technologies as it is always inversely proportionate to QoS (quality of service) in nature. In order to increase the mobile communication system capacity without jeopardizing the system QoS, smart antenna is usually being suggested. There are two major types of smart antenna systems; switch beam antenna and adaptive beam antenna. Adaptive antenna which has dynamic beam is better in improving the system capacity but requires more advance beam forming algorithm and requires intensive processing power. In this paper, a novel adaptive downlink beam forming technique for WCDMA system namely Minimum Downlink Power Consumption (MDPC) is introduced. This MDPC beamforming technique is assisted by Genetic Algorithm (GA) to minimize the downlink power usage at Node B. A dynamic radio network simulator was developed in Visual C++® to study the power consumption at Node B and estimate the downlink capacity improvement by implementing this novel algorithm. Simulation was done based on single micro cell environment with considering interference from the first tier. User mobility is taken into account to provide a combined evaluation of Radio Resource Management (RRM). Capacity system under various simulation scenarios was expressed in downlink outage in this study.